Penerapan Active Building Façade Pada Pekanbaru Cinema Center - Sri Hardianti; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The development of films in Indonesia greatly impact on the enthusiasm of the people in their interest in watching movies in cinemas. People's interest is increasing due to new trends in the world of Indonesian films, which is making sequel of the famous film and remaking some legendary films. This causes the film community as a forum for sharing knowledge about Indonesian films badly needed so that it can be a source of inspiration for filmmakers, as well as increasing the appreciation and pride in Indonesian films. Unfortunately, the growth of the film industry is not offset by the addition of cinema screens. In Pekanbaru, there are only 7 cinemas with a total of 29 screens. Likewise, the film community in Pekanbaru is still not exposed because there is no place to gather and showcase their work to the public. Therefore, a place that can support the people's needs for films is needed, in the form of cinema center as a place for recreation (cinema) and education (film community). The research methods used include field data collection, literature studies and empirical studies. The results of this study are in the form of building design as a place for film activities with the theme of active building facade as a representation of the meaning of the word cinema (derived from Greek, κίνημα) itself, i.e., the motion which also describes the dynamic structure of film.Keywords: Architecture, Cinema Center, Active Building Facade